Bamboo charcoal application altered the mineralization process of soil organic carbon in different succession stages of karst forest land - Hu, Lening; Liu, Xuehui; Xie, Yaqi; Zeng, Yicheng; Ou, Huiping; Yu, Yuefeng; He, Tieguang (Frontiers in Environmental Science, 2024)
As a soil amendment, Bamboo charcoal helps to contributes to the improvement of soil carbon sequestration, but its effect on the accumulation and transformation of different soil organic carbon in soil of karst forests is not clear. The research focused on three distinct forest land succession stages: virgin forest, secondary forest, and planted forest. A 60-day indoor constant temperature culture experiment was conducted, applying bamboo charcoal to the soil of the three forest lands at four different addition ratios: 0%, 1.0%, 2.0%, and 4.0%. The analysis aimed to study the characteristics of SOC mineralization, different carbon fractions of organic carbon, and soil enzyme activity. The findings revealed that bamboo charcoal application led to an increase in the organic carbon (SOC) content within the three forest soils. Moreover, the organic carbon content showed an increase corresponding to the increased proportion of bamboo charcoal, with the highest SOC content observed in the planted forest land with 4.0% bamboo charcoal. The overall performance of the C0/SOC value in the three forest soils was ranked as follows: planted forest < secondary forest < virgin forest (C0: the mineralization potential of soil organic carbon). In both planted and secondary forest soils, the C0/SOC value increased after the application of bamboo charcoal. However, in the virgin forest soil, the application of 1.0% and 4.0% bamboo charcoal reduced the C0/SOC value, while the application of 2.0% bamboo charcoal increased the C0/SOC value. Particularly the C0/SOC value of the planted forest soil without bamboo charcoal was the smallest at 0.047, whereas that in the virgin forest soil with 2.0% bamboo charcoal had the largest value at 0.161. Herein, appropriate human intervention can enhance the carbon sequestration potential of forest soil, in different succession stages within the karst area. However, the external application of bamboo charcoal does not significantly improve the carbon sequestration potential in the planted and secondary forest. Notably, applying a higher proportion (4.0%) of bamboo charcoal can enhance the organic carbon sequestration potential, particularly in the virgin forest soil, representing the climax community of forest succession.